Nilai Kearifan Lokal pada Kesenian Budaya Ondel-ondel di Tanah Betawi (Studi Daerah Khusus Ibu Kota Jakarta) - Susilawati, Efi; Kurnia, Heri (Jurnal Ilmu Sosial dan Budaya Indonesia, 2024)
This study discusses the local wisdom values contained in the ondel-ondel art as part of the Betawi community culture in Jakarta. Ondel-ondel, which originally had a sacred function as a medium to ward off evil spirits, has undergone a transformation in function into a cultural icon and a means of entertainment, especially in the context of tourism and communal celebrations in Jakarta. The purpose of this study is to identify and analyze the local wisdom values in the ondel-ondel art and to understand how the Betawi community interprets and preserves this art in the midst of modernization. The research approach used is descriptive qualitative with data collection techniques through in-depth interviews, field observations, and literature studies. The results of the study show that ondel-ondel contains spiritual, social, and cultural values that reflect the identity of the Betawi community. Spiritual values are seen in the role of ondel-ondel as a symbol of protection; social values are reflected through togetherness and mutual cooperation in making and presenting ondel-ondel; while cultural values are reflected in the use of ondel-ondel as an expression of unique Betawi identity. However, commercialization and changes in the function of ondel-ondel in the modern era have obscured its original meaning, so that preservation efforts are needed so that local wisdom values are maintained. The conclusion of this study emphasizes the importance of the role of communities and governments in preserving ondel-ondel art through educational programs and cultural promotions that maintain its traditional values.